2019
DOI: 10.1002/mrm.28031
|View full text |Cite
|
Sign up to set email alerts
|

CEST MRI quantification procedures for breast cancer treatment‐related lymphedema therapy evaluation

Abstract: PurposeTo quantify chemical exchange saturation transfer contrast in upper extremities of participants with lymphedema before and after standardized lymphatic mobilization therapy using correction procedures for B0 and B1 heterogeneity, and T1 relaxation.MethodsFemales with (n = 12) and without (n = 17) breast cancer treatment‐related lymphedema (BCRL) matched for age and body mass index were scanned at 3.0T MRI. B1 efficiency and T1 were calculated in series with chemical exchange saturation transfer in bilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…The three studies included in this review investigated the use of MRI to quantify therapeutic response to MLD, a common component of the complex decongestive therapy that mobilizes lymph stasis from superficial tissue to deep lymphatic circulation [13]. The effectiveness of MLD remains controversial because detection of changes in lymphedema tissue is difficult with conventional examinations, such as volumetric measurement [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The three studies included in this review investigated the use of MRI to quantify therapeutic response to MLD, a common component of the complex decongestive therapy that mobilizes lymph stasis from superficial tissue to deep lymphatic circulation [13]. The effectiveness of MLD remains controversial because detection of changes in lymphedema tissue is difficult with conventional examinations, such as volumetric measurement [8].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we searched only the PubMed/ MEDLINE and Scopus databases. We also acknowledge that the studies included in this review measured the characteristics of healthy volunteers, which was not described in this study because our analysis was focused on their patients who underwent therapy [8,12,13]. However, this systematic review provides information on the use of MRI to evaluate therapy for BCRL, which is an important topic because of both lymphedema prevalence and debate about the efficacy of lymphedema therapies [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Donahue et al [ 47 ] found APT signals (both standard asymmetry and Lorentzian asymmetry) had no significant difference between the right and left arms of healthy controls but values increased in the patient’s arm that was affected by lymphedema. Crescenzi et al [ 43 ] found that the proton transfer ratio (PTR, defined as 1–Z’, where Z’ is the Z-spectra after B 1 correction) APT significantly correlated with T 1 and BMI (body-mass-index) in controls, and the lymphedema stage in breast cancer treatment-related lymphedema (BCRL) participants. The post-therapy PTR of APT significantly increased in the affected arm of BCRL participants, consistent with the treatment effects that were from mobilized lymphatic fluid.…”
Section: Applicationsmentioning
confidence: 99%